Modelling and Evaluating Air Quality with Fuzzy Logic Algorithm-Ankara-Cebeci Sample - Atacak, Ismail; Arici, Nursal; Guner, Dilem (International Journal of Intelligent Systems and Applications in Engineering, 2017)
Air is one of the most important life sources for all living things. Gases that are present and absent in the composition of clean air also considered as pollutants in the atmosphere. If the pollutants rise above a certain concentration level, air pollution occurs. Air pollution damages all living things, especially human health. Accurate estimation of pollutant concentrations through air pollution modeling has an important effect in reducing the adverse effects of pollution and taking necessary precautions. Conventional statistical models are widely used in air pollution forecasting and modeling. As a different approach, in this study, fuzzy logic algorithm, which has been increasingly successful in many field applications, has been used to model air quality and air pollution analyzes were made based on this model. Ankara -Cebeci province data was used in the sample of the research.